Body temperature monitoring system for activities with controlled artificial cold exposure - Takeda, Fabiano (2019)
The objective of this study was to use a complete system to evaluate the environmental conditions and the thermal discomfort of workers with exposure to low artificial temperatures. The proposed system consists of a wireless sensor network (WSN) using Zigbee technology, providing a set of sensors to simultaneously measure body temperature in different regions of the body of workers exposed to low temperatures and to measure the environmental conditions that influence the evaluation of thermal discomfort. The data was collected by a Zeegbee USB module connected to a Windows PC and the results are recorded and displayed in real time. The study was carried out with evaluations in 153 workers of cut line of a refrigerator of slaughter and cuts of chickens. The presented system has been proven as an easy and quick to install and reliable way to assess artificial cold exposure. The results showed that although the activity represents an adequate PMV, in compliance with national legal and normative criteria, the results of the finger and the hallux show conditions of cold and pain during almost every working day.